EKSEKUSI ‘Ab INTESTATO’ WARISAN DUA BANDING SATU: RASIONALISASI SURAH ANNISA AYAT 11 - Rasyid, Idris (DIKTUM: Jurnal Syariah dan Hukum, 2016)
In Inheritance laws, principle is applicable. If someone dies, then all rights and obligations switch to the heirs. This principle is stated in a French proverb "le mort saisit le vif", while the measurement of all the rights and obligations of the deceased by heirs was called "saisine". Heir is any person who is entitled to inheritance of heir and obliged to resolve the debt. The rights and obligations arising after the testator dies. Inheritance rights was based on the relationship of marriage, blood ties, and testament, which is set in law. Rationalization division of 2:1: male is responsible for zuriyat (offspring). He was in charge of keeping nasab of his father, the elder men in the family then, the obligations as men are so severe that God prepare them more than women. While women get inheritance for himself because she has become the responsibility of husband.